The rumen microbiome: an underexplored resource for novel antimicrobial discovery. (December 2017) - Oyama, Linda; Girdwood, Susan; Cookson, Alan; Fernandez-Fuentes, Narcis; Privé, Florence; Vallin, Hannah; Wilkinson, Toby; Golyshin, Peter; Golyshina, Olga; Mikut, Ralf; Hilpert, Kai; Richards, Jennifer; et al.
Abstract Antimicrobial peptides (AMPs) are promising drug candidates to target multi-drug resistant bacteria. The rumen microbiome presents an underexplored resource for the discovery of novel microbial enzymes and metabolites, including AMPs. Using functional screening and computational approaches, we identified 181 potentially novel AMPs from a rumen bacterial metagenome. Here, we show that three of the selected AMPs (Lynronne-1, Lynronne-2 and Lynronne-3) were effective against numerous bacterial pathogens, including methicillin-resistantStaphylococcus aureus (MRSA). No decrease in MRSA susceptibility was observed after 25 days of sub-lethal exposure to these AMPs. The AMPs bound preferentially to bacterial membrane lipids and induced membrane permeability leading to cytoplasmic leakage. Topical administration of Lynronne-1 (10% w/v) to a mouse model of MRSA wound infection elicited a significant reduction in bacterial counts, which was comparable to treatment with 2% mupirocin ointment. Our findings indicate that the rumen microbiome may provide viable alternative antimicrobials for future therapeutic application. Antibiotics: Potential in the rumen Anti-microbial molecules made by microbes in the gut of ruminant animals could become new weapons against antibiotic-resistant infections. An international team of researchers led by Sharon Huws at Queen's University Belfast, UK, identified three anti-microbial peptides in the rumen of animals such as cattle, sheep and goats. The peptides—short proteins—were highly active in laboratory trials against several clinically important drug-resistant infections. These included methicillin resistantStaphylococcus aureus (MRSA), a notorious cause of life-threatening infections, especially in patients with weakened immunity. There is growing interest in using peptides as alternatives to existing antibiotics. The findings, initiated by examining a 'library' of molecular data, suggest that the rumen is an under-explored resource that may harbor many medically useful antimicrobials. The possibilities should be investigated further, with promising molecules being tested in clinical conditions.